Legal Protection for Public Accountants in the Framework of Maintaining the Independence and Objectivity of Financial Report Audits - Saleh, M.; Riswadi, Riswadi (International Journal Labs, 2025)
Public accountants play a critical role in ensuring the reliability and transparency of financial reports, yet they often face pressures that threaten their independence and objectivity. This study examines the legal protections available to public accountants in Indonesia, focusing on the effectiveness of existing regulations in safeguarding their professional integrity. Using a normative juridical method, the research analyzes key legal instruments, including Law Number 5 of 2011 on Public Accountants, Government Regulation Number 20 of 2015, and OJK Regulation Number 9 of 2023, alongside professional standards and ethical codes. Findings reveal that while preventive protections, such as ethical guidelines and transparency mechanisms, and repressive measures, like dispute resolution through the Professional Advisory Council (DPP), are in place, challenges persist. These include weak enforcement of ethical standards, legal ambiguities in liability cases, and insufficient oversight by regulatory bodies like the Financial Services Authority (OJK). The study highlights the need for stronger regulatory frameworks, enhanced supervisory capacities, and greater awareness among stakeholders about the importance of auditor independence. Recommendations include harmonizing national standards with international practices, improving transparency in professional dispute resolution, and fostering a culture of ethical accountability. Strengthening these areas is essential to uphold the integrity of financial audits and maintain public trust in the financial system.